(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The article presents the forms and ways in which the cultural transmission of Zofka Kveder took place. It explains in which cultural spaces she worked and how she established personal contacts with artists. Zofka Kveder worked in a multidirectional way, as she promoted Slovene culture in the new cultural environments she moved into, and acquainted the Slovene cultural space with the achievements of foreign artists. She was also a mediator of ideas: feminism, Yugoslavism, and ideas about coexistence and mutual respect between different cultures. Zofka Kveder’s translation oeuvre is very rich and almost unexplored so far, which opens up possibilities for new research.